2019
DOI: 10.1590/1678-4685-gmb-2018-0073
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21 over expression in umbilical cord blood hematopoietic stem progenitor cells by leukemia microvesicles

Abstract: Microvesicles are able to induce the cell of origin’s phenotype in a target cell. MicroRNA-21, as an oncomir, is up-regulated in almost all cancer types such as leukemia which results in cell proliferation. In this study, we examine the ability of leukemia microvesicles to induce proliferation in hematopoietic stem progenitor cells (HSPCs) via microRNA-21 dysregulation. Herein, leukemia microvesicles were isolated from HL-60 and NB-4 cell lines by ultracentrifugation, and then their protein content was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…There is increasing evidence of a leukemia-like phenotype induction in normal hemopoietic stem/progenitor cells by leukemia EVs. A recent study demonstrated the ability of EVs derived from leukemia cells (HL-60 and NB-4 cell lines) to induce proliferation of cord blood-derived CD34+ cells via miR-21/miR-29 dysregulation [ 89 , 90 ].…”
Section: Ev Regulation On Normal Hemopoiesis Restrain/transformatimentioning
confidence: 99%
“…There is increasing evidence of a leukemia-like phenotype induction in normal hemopoietic stem/progenitor cells by leukemia EVs. A recent study demonstrated the ability of EVs derived from leukemia cells (HL-60 and NB-4 cell lines) to induce proliferation of cord blood-derived CD34+ cells via miR-21/miR-29 dysregulation [ 89 , 90 ].…”
Section: Ev Regulation On Normal Hemopoiesis Restrain/transformatimentioning
confidence: 99%
“…For functional experiments, we treated HSPCs with two doses of EVs based on protein quantification (and not on particle number). Interestingly, the EV amount used (20 and 40 μg to treat 1 × 10 5 HSPCs) was in line with that used in another context such as that of AML-EVs and HSPCs where it was defined as a very small amount to induce effects in cells ( 29 ).…”
Section: Discussionmentioning
confidence: 70%
“…We directly evaluated the influence of miRNAs on cell fate decisions in bulk human CD34 + cells following exposure to MM-EVs. We focused our attention on miR-21, miR-34a, miR-150, and miR-155, since they are the important mediators in hematopoietic stem cell differentiation and proliferation and, also, in the “malignancy-like transformation” of HSPCs ( 29 , 40 44 ). Lu et al ( 45 ) examined human BW-derived MEPs to identify miRNAs that influence cell fate choice between megakaryocytes or erythrocytes with the identification of miR-150 as crucial in this process.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, MSC-derived MVs lack MHC class I and II, which allows allogenic transfusion without eliciting autoimmunity or tumors [ 98 , 130 ]. MSC-derived MVs were shown to circulate in the blood and contain molecules, including miRNA, with potential therapeutic properties [ 131 ]. Collino et al have also demonstrated that MSC-derived MVs can hold ribonucleoproteins involved in the intracellular trafficking of RNA as well as selected miRNAs [ 132 ].…”
Section: Mesenchymal Stem Cell (Msc)-derived Mvsmentioning
confidence: 99%